Revealing and explaining deep structure via Qualitative Research in Medicine and Healthcare - Warren Bareiss (Qualitative Research in Medicine & Healthcare)
In the previous issue of this journal (Volume 5, Issue 3), I described Qualitative Research in Medicine & Healthcare as a “helping journal.” By that, I meant that QRMH welcomes manuscripts from a range of specializations, and as editor, I am glad to assist writers wherever they are within that range. [...]